The Effect of Nickel to Manganese Ratio and the Matrix Phase on the Properties of W-Ni-Mn Tungsten Heavy Alloys - Mahdi Rajaee; Mahdi Raoufi; Zeinab Malekshahi Beiranvand; Abbas Naeimi (Iranian Journal of Materials Science and Engineering)
This research explored the impact of the nickel-to-manganese ratio and the influence of the matrix phase on the properties of W-Ni-Mn tungsten heavy alloys (WHAs), aiming to determine the optimal composition for achieving desirable alloy properties.  For this purpose, tungsten, nickel, and manganese powders with specified weight percentages underwent two rounds of wet milling.  Powder mixtures were obtained with weight ratios of 90W-6Ni-4Mn, 90W-8Ni-2Mn, and 88W-10Ni-2Mn. These mixtures were then compressed through the cold pressing method at a pressure of 250 MPa. Subsequent reduction and sintering processes were carried out in a tube furnace at temperatures of 1150 and 1400 °C, respectively. Microstructural characterization was conducted using both optical and electron microscopy. The results showed that the change in chemical composition is not significantly effective on the sintering density of the samples and also the highest sintering density, reaching 90.11%, was achieved with the 88W-10Ni-2Mn sample. Furthermore, the results demonstrated that carburization of W-Ni-Mn WHAs during the sintering process led to an increase in the micro-hardness of the samples. The highest hardness, measuring 381 Hv, was observed in the 90W-6Ni-4Mn alloy, where carburization occurred. XRD results revealed that an increase in the nickel-to-manganese ratio led to a reduction in the peaks of manganese carbide and tungsten carbide. Consequently, this decrease in carbide peaks resulted in a reduction in hardness, reaching 352 Hv in the case of the 88W-10Ni-2Mn sample. Additionally, the alloys 90W-6Ni-4Mn and 88W-10Ni-2Mn both exhibited the lowest continuity, a value of 0.5. Fracture surface SEM images illustrated that the 90W-6Ni-4Mn alloy, characterized by the lowest nickel-to-manganese ratio (1.5), exhibited the highest trans-granular fracture mode involving cleavage and matrix tearing, which is considered desirable. Furthermore, an increase in the matrix phase content resulted in a shift of the preferred crack path, originating from the matrix phase.